Analisis Pengaruh Digital Marketing Melalui Media Sosial Terhadap Peningkatan Brand Awareness Satisfaction dan Customer Loyalty di PT Mayora Indah - Darwin Yulian; Umbas Krisnanto (Sekolah Pascasarjana Perbanas Jakarta, 2021)
The purpose of this study was to obtain information and data relating to factors that influence Brand Awareness, Customer Satisfaction and Customer Loyalty at PT Mayora Indah Tbk. Discussion of the problem that will be presented by the author is inseparable from the objectives to be achieved. The research method used in this study is descriptive and verification research methods with quantitative approaches. Primary data used in this study are data collected by researchers based on questionnaires distributed to respondents in this case are consumers in PT Mayora Indah Tbk in the form of a statement filled based on the answer choices provided. The scale used in this research instrument is the Likert scale. Based on the results of data analysis and discussion previously explained about the analysis of the effect of digital marketing strategies through social media on increasing brand awareness, customer satisfaction and customer loyalty at PT Mayora Indah Tbk, the conclusions here will provide answers to the objectives of this study, The research objective is to analyze digital marketing through social media, Brand Awareness, Customer Satisfaction and Customer Loyalty at PT Mayora Indah Tbk, which is a digital marketing strategy that is measured by Brand Exposure variables, Customer Engagement, Electronic Word of Mouth based on descriptive calculations. The Exposure brand is included in the good category which means that the strategy prepared by PT Mayora Indah Tbk for Kis candy products sold in order to build brand awareness has been valued by consumers. In addition, Customer Engagement is included in the good category so that the process of PT Mayora Indah Tbk on Kis candy products to provide opportunities for consumers to engage and interact in two-way communication so that they can create an interactive dialogue and provide personal experiences that customers will remember said good.